Primary institutions and security in Andean Community: exploration from the English School perspective - Guerrero Salgado, Gilda Alicia (Instituto de Altos Estudios Nacionales IAEN, 2024)
This article explores why the Andean Community of Nations (CAN) has failed to achieve concrete regional security strategies for member countries. The research uses the English School of International Relations approach that considers security a value or a "primary institution", like territoriality, sovereignty, equality, and market; therefore, agendas and discussions within the regional group should include security proportionally. Through a frequency analysis, the study reviewed 342 decisions adopted by the CAN during 2006-2020. The results show that the community is still consolidating its structure. Although CAN has a broad technical agency and a scheme dedicated to strengthening the common market, its system of primary institutions is weak. In this sense, decisions on security are insufficient.